2013
DOI: 10.12988/asb.2013.31043
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cadmium oxide nanoparticles on pseudomonas aeruginosa bacteria

Abstract: For many centuries, the metals are used as the antibacterial factors. Whereas, the nanoparticles are mostly heavy metal oxides, they have a high tendency to interact with biological molecules and develop the deactivation or elimination of the virus or bacteria. In the present study, the antibacterial effect of Cadmium Oxide nanoparticles on Pseudomonas Aeruginosa bacteria was analyzed which are considered some sort of resistant bacteria against antibiotics now. The aim of his study was to investigate the antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…For P. aeruginosa , growth on agar plates was observed for all pH values above pH 3.3 (overgrown after overnight incubation) and no growth was observed for pH values below pH 3.2 (no colonies visible), indicating a change in physiology at these pH values. This result is comparable with the result of another study investigating the effect of low pH values on the survival of P. aeruginosa [ 31 ] while a different study found good bacterial growth for pH higher than 3.8 [ 32 ]. For all filtrations, the cultivated P. aeruginosa samples were acidified before filtration and the optimized protocol (MAF-OH, 5-L initial sample volume, BEG elution buffer) was used.…”
Section: Resultssupporting
confidence: 89%
“…For P. aeruginosa , growth on agar plates was observed for all pH values above pH 3.3 (overgrown after overnight incubation) and no growth was observed for pH values below pH 3.2 (no colonies visible), indicating a change in physiology at these pH values. This result is comparable with the result of another study investigating the effect of low pH values on the survival of P. aeruginosa [ 31 ] while a different study found good bacterial growth for pH higher than 3.8 [ 32 ]. For all filtrations, the cultivated P. aeruginosa samples were acidified before filtration and the optimized protocol (MAF-OH, 5-L initial sample volume, BEG elution buffer) was used.…”
Section: Resultssupporting
confidence: 89%
“…The synthesis of nanoparticles was done by using the ratio 1:1 of cyanobacterial extract : chloro auric chloride (HAucl4) (1) mM (13) using magnetic stirrer at (80) C for (15) min until color of the reaction mixture change from pale yellow to purple ( Fig 3) .…”
Section: Synthesis Of Gold Nanoparticlesmentioning
confidence: 99%
“…The synthesized gold nanoparticles as antibacterial activity of synthesized AuNps were studied using the turbidity methods (15) .…”
Section: Antibacterial Activity Assaymentioning
confidence: 99%
“…Nanoparticles of heavy metals as metal oxides have a high ability to interact with pathogenic microorganisms and deactivate or eliminate the virus or bacteria especially P. aeruginosa (Salehi et al, 2013;and Chauhan et al, 2014). Effectiveness of nanoparticles as antimicrobial agents was due to small doses used, low toxicity and lack of side effects (Lara et al, 2010) and its bactericidal activity depends on their concentration, their stability, and size of nanoparticles (Raghupathi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%